The evolving role of cardiovascular magnetic resonance in the assessment of mitral valve prolapse - Vermes, Emmanuelle; Altes, Alexandre; Iacuzio, Laura; Levy, Franck; Bohbot, Yohann; Renard, Cédric; Grigioni, Francesco; Maréchaux, Sylvestre; Tribouilloy, Christophe (Frontiers in Cardiovascular Medicine, 2023)
Mitral valve prolapse (MVP), characterized by a displacement > 2 mm above the mitral annulus of one or both bileaflets, with or without leaflet thickening, is a common valvular heart disease, with a prevalence of approximately 2% in western countries. Although this population has a generally good overall prognosis, MVP can be associated with mitral regurgitation (MR), left ventricular (LV) remodeling leading to heart failure, ventricular arrhythmia, and, the most devastating complication, sudden cardiac death, especially in myxomatous bileaflet prolapse (Barlow's disease). Among several prognostic factors reported in the literature, LV fibrosis and mitral annular disjunction may act as an arrhythmogenic substrate in this population. Cardiac magnetic resonance (CMR) has emerged as a reliable tool for assessing MVP, MR severity, LV remodeling, and fibrosis. Indeed, CMR is the gold standard imaging modality to assess ventricular volume, function, and wall motion abnormalities; it allows accurate calculation of the regurgitant volume and regurgitant fraction in MR using a combination of LV volumetric measurement and aortic flow quantification, independent of regurgitant jet morphology and valid in cases of multiple valvulopathies. Moreover, CMR is a unique imaging modality that can assess non-invasively focal and diffuse fibrosis using late gadolinium enhancement sequences and, more recently, T1 mapping. This review describes the use of CMR in patients with MVP and its role in identifying patients at high risk of ventricular arrhythmia.